The Influence of Journaling On Self-Actualization and Creative Expression - Ann G. Williamson (REGIS UNIVERSITY, 2023)
This project is intended to comment on the importance and affect of keeping a journal on the process of becoming self actualized and in the creative expression endeavor from a feminine perspective. It is this author’s perception that keeping a journal is a relevant and crucial factor in these two areas of human development. Journaling aids in critical, analytical, reflective thinking and affords an opportunity for creative expression as evidenced by the large number of published journal keepers. The life and writings of Virginia Woolf is used as a case study. Her life and collected writings support the premises noted above. Included in this project is the author’s novel, a work that embraces and evidences the beneficial outcomes of keeping a journal.